SMP ALAM MUHAMMADIYAH INDRASARI MARTAPURA - Yahya, Muhammad; Saud, Mohammad Ibnu (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
We can now easily find natural schools at the elementary level in every district and city in South Kalimantan. Meanwhile, there are still very few natural schools at the next level, including junior high school. It was on this basis that the presence of a natural junior high school was felt to be very necessary, then this was responded to quickly by the administrators of the Alam Muhammadiyah Indrasari Martapura Elementary School of Akhlak who wanted the establishment of the Alam Muhammadiyah Indrasari Martapura Middle School. The design of SMP Alam Muhammadiyah Indrasari Martapura must pay attention to the curriculum structure that has been created by the development preparation team, which wants the best graduates to have strong character and knowledge that is oriented towards good morals. Through the learning media programming method, the design of SMP Alam Muhammadiyah Indrasari Martapura can be translated into a design strategy. Using the concept of space flexibility can be a problem solver in design. By implementing the concept of space flexibility, the design plan for SMP Alam Muhammadiyah Indrasari can accommodate teaching and learning activities at this natural school. The application of design methods based on learning media with the concept of flexibility can form characters in children who are morally oriented and exemplary to create a generation that cares about the natural and social environment.